HARMONISASI INTERPELASI DEWAN PERWAKILAN RAKYAT TERHADAP KEBIJAKAN PEMERINTAH - Shobahah, Nurush (Ahkam: Jurnal Hukum Islam, 2016)
The House of Representatives as a legislative body has three functions, namely the oversight function, legislative function, and the budget function. One of the supervisory function s of The House of Representatives is the right of interpellation. As a law state, all of the processes of the state must be based on the law. Therefore, every positive law must be obeyed. The constitutions or other regulations of interpellation mention that the president may represent the answers of interpellations. The frequent problem happening is the absence of the president in the interpellation session. That problem becomes a relation problem between the president and the House of Representatives which need to solve. Thus the right of interpellation as one of the implementations of the check-and-balance principle on these two state institutions can run effectively. Based on the normative provision study it can be concluded that, to avoid the messy practices, the chapter which allows the president to have position in answering the interpellation court needs to be specified explicitly. As the result, the right of using interpellation can run well. Kata kunci: Dewan Perwakilan Rakyat, Interpelasi, Presiden